The effect of organisational internal factors and technology orientation on environmental sustainability performance of Malaysian construction firms - Ajibike, Waliu Adeniyi (2021)
Construction organisations worldwide are under pressure to minimise resource consumption and prioritise the call for environmentally responsive projects. Within the Malaysian construction industry, the fundamental elements of organisational internal factors (such as managerial attitudes, social responsibility, and company culture), technological orientation, and coercive pressures have not been thoroughly researched as preconditions for construction firms to attain environmental sustainability. This study seeks to fill this gap by applying the contingency resource-based view, institutional, and learning theories to investigate the effects of organisational internal factors and technology orientation on construction firms’ environmental sustainability performance. The study also considered the intervening role of coercive pressure. A total of 185 construction firms from the eleven states in the peninsula Malaysia (the Federal Capital Territory of Kuala Lumpur inclusive) participated in the online survey. After the data screening using SPSS (version 26), the Partial Least Squares Structural Equation Modeling (PLS-SEM) algorithm and bootstrap techniques were utilised to test the hypothesised paths in this study. The empirical evidence supported the hypothesised direct and indirect effects of managerial attitudes, social responsibility, and company culture on environmental sustainability performance. Also, there is a strong positive effect of company culture on environmental sustainability. This relationship suggests that when construction firms integrate environmental culture, their environmental sustainability performance increases. This finding conforms with the contingency resource-based view theory, which submits that a firm's culture is a viable source of continual competitive advantage and that firms with robust cultures are viewed as exemplars of excellent management. Similarly, this study's findings also established that coercive pressure is a positive mediator and a catalyst that plays a complementary role between managerial attitudes, company culture, social responsibility, technology orientation, and environmental sustainability performance. This shows the impact of government pressure in ensuring that rules and regulations are followed in project delivery. Hence, to ensure environmental sustainability in construction project delivery, more emphasis is recommended to improve top managers' attitudes, social responsibility, and company culture towards the natural environment. Simultaneously, government agencies need to be strengthened to ensure that construction regulations are strictly adhered to.